Analysis of Quality of Service (QOS) on Whole Home Mesh Network with Wifi Connection - Khalifattaqi, M. Radhian (Journal of Social Science, 2024)
Advances in network technology are increasingly developing. Due to the human need for fast, easy and comfortable access to technology. So there is competition between network device manufacturers to innovate in creating new, compact technology, especially after the emergence of AI technology which has been trying to be embedded in various devices recently. Mash technology is nothing new in the networking world. However, problems that often occur with Mesh devices include compli-cated installation and requiring different types of devices and some-times with different brands there is quite noticeable latency. Whole Home Mash (WHM) is a technology made by TP-LINK which is embed-ded in DECO series devices which have various contemporary features such as WiFi 6, OFDMA and MU-MIMO which can facilitate device connections in accessing the internet. What is focused on in this re-search is the WiFi or wireless-based Mesh feature which makes this device very easy to install and the settings are supported by an App that can be accessed from the user's cellphone. Based on the Quality of Service (QoS) assessment criteria which consist of: Throughput, Delay, Jitter and Packet Loss, each of which gets a score of 4 in the index which means it is in the very good category. The results show that in 4 times with different conditions and distances it met criteria 4 (very good) in Throughput, Delay, Jitter but experienced a decrease in Pack-et Loss with the "moderate" criteria for data sizes above 400 MB. In short, this device meets index 4 of the four criteria above and can be a reference in modeling a WiFi-based network in the future.